Manajemen Pondok Pesantren Dalam Pembentukan Karakter Kemandirian Entrepreneur Santri Pondok Pesantren Salafiyah Baitul Kirom Lampung Selatan - Syarifudin, Amat; Yetri, Yetri; Thahir, Andi (El-Idare, 2023)
This study aims to describe and analyze in depth the management of Islamic boarding schools in the formation of the entrepreneurial character of the independent students of the Salafiyah Baitul Kirom Islamic Boarding School, South Lampung, starting from the formation strategy, efforts, and forms of entrepreneur education. This research is a field research with a qualitative approach. Data collection techniques using observation, documentation and interviews. Data analysis uses an interactive model consisting of data collection, data reduction, data presentation, and drawing conclusions. The results showed that: (1) The strategy for forming the independent character of santri entrepreneurs is first, by learning by doing (learning while working) or direct practice, second, there is entrepreneurial management by caregivers which includes training, mentoring and evaluation (2) Efforts in the formation of the character of the independence of the santri entrepreneur by forming initiative skills, overcoming obstacles and problems, self-confidence, doing business without the help of others and being responsible, (3) The character education program for the independence of the santri entrepreneur includes the business of clothing convection, laundry, oyster mushroom cultivation, fishery, cooperatives (canteens), mineral water depots and agriculture.